The pro-cyclicality of loan loss provisions: Evidence from selected east Asian countries - Abdul Adzis, Azira (Universiti Utara Malaysia, 2017)
This study investigated the evidence of pro cyclical behaviour of loan loss provision in four East Asian countries, namely Malaysia, Thailand, Singapore, and Hong Kong for the period 1995-2009. Pro-cyclical is defined as building up more loan loss provision during the bad times and reducing them in good times.This study hypothesized that pro-cyclical behaviour of loan loss provision exists in East Asian countries, since they had experienced two types of financial crises – Asian financial crisis in 1997 and global economic crisis in 2008.Utilising a sample of 47 banks, the findings demonstrated that there is evidence of a pro-cyclical pattern in the countries studied, as shown by the negative relationship between loan loss provision and GDP.This study does have a policy implication, where bank regulators should take pro-active action in addressing the issue of pro-cyclicality of loan loss provision because in bad times, increasing loan loss provision would affect the bank’s profit, weaken the bank’s capital, and in turn, diminish its lending activities to creditworthy borrowers.